The Influence of Health Education on Diabetes Mellitus on Knowledge Improvement of Diabetes Mellitus Cadres in the Working Area of Medokan Ayu Health Center, Surabaya, Indonesia - Andajani, Susilowati (Folia Medica Indonesiana, 2019)
This study aimed to analyze the influence of health education on improcing health cadres' knowledge about Diabetes Melitus (DM) at Ayu Medokan Health Center, Surabaya, Indonesia. The type and design of this study was non-randomized pretest-posttest design, with samples of DM cadres in the working area of Medokan Ayu Health Center, Surabaya, Indonesia. Sample size was 24 persons. The treatment variable was health education, while the dependent variable was the increase of the cadres' knowledge about DM. Normality test was performed with Kolmogorov Smirnov (a=0.05) and data analysis with Paired t-test (a=0.05). This study found that DM cadres were mostly female (23 people), with the youngest age 24 years, and the oldest 61 years. The highest age group (45.80%) was 40-49 years with a mean age of 44.37 + 9.27 years. Most of DM cadres' education (62.5%) was senior high school, then junior high school (25%). Most (58.3%) of the DM cadres did not work or as housewives. Besides being a DM cadre, most of them also posyandu and bumantik cadres, 2) There was a significant difference (p<0,0001) between the level of knowledge before and after health education. In conclusion, cadres' knowledge about DM can be improved, among others, by providing health education.